Hit-to-lead optimization of a benzene sulfonamide series for potential antileishmanial agents. Issue 11 (25th August 2020) - Koovits, Paul J.; Dessoy, Marco A.; Matheeussen, An; Maes, Louis; Caljon, Guy; Ferreira, Leonardo L. G.; Chelucci, Rafael C.; Michelan-Duarte, Simone; Andricopulo, Adriano D.; Campbell, Simon; Kratz, Jadel M.; Mowbray, Charles E.; et al.
Abstract : A series of benzene sulphonamides with good potency and selectivity against Leishmania spp. intracellular amastigotes was identified by high-throughput screening. Abstract : A series of benzene sulphonamides with good potency and selectivity against Leishmania spp. intracellular amastigotes was identified by high-throughput screening. Approximately 200 compounds were synthesized as part of a hit-to-lead optimization program. The potency of the series appears to be strongly dependent on lipophilicity, making the identification of suitable orally available candidates challenging due to poor pharmacokinetics. Despite not identifying a clinical candidate, a likely solvent exposed area was found, best exemplified in compound 29 . Ongoing detailed mode-of-action studies may provide an opportunity to use target-based medicinal chemistry to overcome the issues with the current series.